ICT Utilization As Correlates Of Academic Performance Among Students With Visual Impairment In Lagos State, Nigeria - Eguavoen, Edward O. (European Scientific Journal, ESJ, 2016)
Vision, an essential part of human existence plays vital roles in the life of an individual and any hindrance to vision resulting in total or partial loss of sight creates difficulties in understanding the world around such an individual. The problem associated with academic performance of students with visual impairment has a number of indicators which have not received adequate attention from researchers in special education. This study therefore, examined the relationship of information and communication technology (ICT) utilisation on academic performance of students with visual impairment in Lagos State. The objectives of the study were to identify ICT tools, level of ICT utilisation as well as their relationship to academic .performance among students with visual impairment. Using descriptive research design of correlational type, twenty eight students with visual impairment were selected using purposive sampling technique from two special schools located within Lagos state. A structured questionnaire was used to elicit information from the respondents and data obtained were analysed using descriptive statistics and Pearson product moment correlation statistics. Two research questions were raised while one hypothesis was generated and tested at 0.05 level of significance. The results indicated that there was significant relationship between information and communication technology utilisation and academic performance of students with visual impairment in Lagos state (r = .536, P< .05). Based on the findings of the study, it is recommended that schools should adopt appropriate ICT tools that will enhance academic performance of students with visual impairment and to include ICT training skills in the curriculum of special schools.